2015
DOI: 10.1097/jnr.0000000000000082
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With the Development of Delirium in Elderly Patients in Intensive Care Units

Abstract: Delirium is a severe problem among elderly patients in the ICU. Healthcare professionals should pay more attention to elderly patients at greater risk for experiencing delirium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 0 publications
0
19
1
3
Order By: Relevance
“…The prevalence of 16% observed in our study was much smaller than previous studies in which from 30% to approximately 55% of critical care patients presented delirium [15,16].…”
Section: Potential Selection Biascontrasting
confidence: 77%
“…The prevalence of 16% observed in our study was much smaller than previous studies in which from 30% to approximately 55% of critical care patients presented delirium [15,16].…”
Section: Potential Selection Biascontrasting
confidence: 77%
“…It was evidenced that the updating of the topic of training nurses in intensive care units increased the recognition rate among professionals and suggested that the strategy should be kept, as well as the routine evaluation of patients with potential for confusional conditions, with the aid of validated tools and non-pharmacological measures for prevention and management of delirium. 3,14 It was found during workshops conducted in a study that the knowledge of the team about delirium was superficial, although practices of reorientation in time and space and sleep promotion were performed to prevent the disorder. 21 It was noticed that the low number of studies about the realization of educational interventions points out the need for more such actions in order to train the teams and reduce the incidence of delirium in ICUs.…”
Section: Importance Of Educational Interventions With Nursing Teams Imentioning
confidence: 99%
“…13 It is understood that the nursing team has a primary role in the prevention and detection of delirium because nursing is the professional category that provides direct health care and accompany patients 24 hours a day, mainly in ICUs. 7,[14][15] It has been observed that the development of non-pharmacological measures is fundamental in the management and prevention of delirium. [16][17] It is noted that the implementation of educational interventions with nurses in ICUs contributes to improve their knowledge and skills on the recognition of the problem and its standardized evaluation.…”
mentioning
confidence: 99%
“…42 Nitrik oksit gazı, santral ve periferik sistemde serbest oksijen radikali ve nörotransmitter olarak görev yapar. 43 Sezer ve ark.nın koroner baypas ameliyatı geçiren hastalarda deliryum gelişiminin nitrik oksit düzeyleriyle ilişkisini inceledikleri çalışmada, koroner baypas ameliyatı olan hastalarda ameliyat sonrası nitrik oksit düzeylerinin arttığı, deliryum gelişenlerde ise bu artışın daha fazla olduğu bildirilmiştir. 10 Deliryum gelişen hastalarda nitrik oksit düzeylerinin aşırı yüksek olması, bu hastalarda serebral iskeminin daha fazla olması ve beyin dokusunun ameliyata bağlı oksidatif strese daha şiddetli reaksiyon vermesi ile açıklanmıştır.…”
Section: *Solunumunclassified